Epigenetic regulation of cancer stemness - Claudia Galassi; Gwenola Manic; Manel Esteller; Lorenzo Galluzzi; Ilio Vitale (Signal Transduction and Targeted Therapy)
Abstract Gene expression is finely controlled by the abundance and activation status of transcription factors and their regulators, as well as by a number of reversible modifications of DNA and histones that are commonly referred to as epigenetic marks. Such alterations (i.e., methylation, acetylation, and ubiquitination) are catalyzed by an array of dedicated enzymes with antagonistic activity, including methyltransferases and demethylases, acetyltransferases and deacetylases, as well as ubiquitin ligases and deubiquitinating enzymes. The epigenetic control of transcription is critical not only for embryonic and postembryonic development but also for the preservation of homeostasis in all adult tissues. In line with this notion, epigenetic defects have been associated with a variety of human disorders, including (but not limited to) congenital conditions as well as multiple hematological and solid tumors. Here, we provide an in-depth discussion of the impact of epigenetic alterations on cancer stemness, i.e., the ability of a small population of poorly differentiated malignant cells to (1) self-renew while generating a more differentiated progeny, and (2) exhibit superior tumor initiating/repopulating potential along with exceptional plasticity and improved resistance to environmental and therapy-elicited stress. Moreover, we critically evaluate the potential and limitations of targeting epigenetic modifiers as a means to eradicate cancer stem cells for therapeutic purposes.